2005
DOI: 10.1111/j.1440-1746.2005.04061.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological implications of hepatitis C virus diagnosis

Abstract: Diagnosis with HCV is reported to be more stressful than divorce, loss of source of income and a move to another city.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
(21 reference statements)
0
13
0
2
Order By: Relevance
“…However, the responses of study participants were almost evenly divided between those who described diagnosis as distressing and those who reported being unconcerned. Due to a focus in the literature on diagnosis as disruptive, both in regard to hepatitis C (Krug 1995, Burrows and Bassett 1996, Hepworth and Krug 1999, Glacken et al 2001, Gill et al . 2005) and chronic illness more generally (Bury 1982, Mathieson and Stam 1995, Wilson 2007), this paper will focus on the experiences of the 21 participants who described their experience of diagnosis as of ‘no big deal’.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the responses of study participants were almost evenly divided between those who described diagnosis as distressing and those who reported being unconcerned. Due to a focus in the literature on diagnosis as disruptive, both in regard to hepatitis C (Krug 1995, Burrows and Bassett 1996, Hepworth and Krug 1999, Glacken et al 2001, Gill et al . 2005) and chronic illness more generally (Bury 1982, Mathieson and Stam 1995, Wilson 2007), this paper will focus on the experiences of the 21 participants who described their experience of diagnosis as of ‘no big deal’.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies addressing hepatitis C diagnosis report that a majority of respondents found diagnosis to be stressful and distressing. Reactions included feeling ‘shocked’, ‘devastated’, ‘unclean’ and ‘contaminated’, with the word ‘leper’ a frequent descriptor (Krug 1995, Burrows and Bassett 1996, Hepworth and Krug 1999, Glacken 2001, Harris 2005, Gill et al . 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since HCV is a single-stranded RNA virus that mutates or replicates very rapidly, this disease is difficult to treat and individuals are faced with the fact that hepatitis C is a chronic, progressive disease that does not yet have a cure. A diagnosis of hepatitis C has been found to cause significant stress for newly diagnosed patients and has been reported to be more stressful than divorce, loss of source of income, or a move to another city (Gill, Atiq, Sattar & Khokhar, 2005). High levels of psychological distress and impaired quality of life have been found in patients with hepatitis C (Coughlan, Sheehan, Hickey & Crowe, 2002;Gifford, O'Brien, Bammer, Banwell, & Stoove, 2003).…”
Section: Depressionmentioning
confidence: 98%
“…A study of 98 newly diagnosed individuals in Islamabad by Gill, Atiq, Sattar, and Khokhar (2005) found that HCV diagnosis was significantly more stressful than divorce and loss of source of income. A study of 98 newly diagnosed individuals in Islamabad by Gill, Atiq, Sattar, and Khokhar (2005) found that HCV diagnosis was significantly more stressful than divorce and loss of source of income.…”
Section: Related Literaturementioning
confidence: 99%